A dimensão estética da experiência na educação infantil : uma proposta de instalação artística - Silva, Simone de Cássia Soares da (2019)
In contemporary times, day care presents itself as fertile ground for discussions about education, childhood, language and aesthetics, among other themes inherent to the integral needs of children in formation. We found in the National Curriculum Guidelines for Day Care Education, consolidated in resolution 05/2009, prescriptions about the languages to be approached in this educational modality, guided by jokes and interactions. This assumption leads us to think about how the child relates individually and collectively, expresses and expands the potentialities of apprehending and meaning the world; a reflexive challenge that involves pedagogical, sociological, aesthetic and even political conceptions about the context of Day Care Education, especially among these, reflection on languages. In this perspective, artistic experiences can act as guides to education in infancy, because they produce meanings that dialogue intimately in the appearance of languages, produce multiple literacies and express the subjectivity of being in the knowledge of oneself and the world around them. Thus, the present work, linked to the research line "Languages, Culture and Knowledge Construction: Historical and Contemporary Perspectives" and the research group ALFALE - Alfabetização e Letramento Escolar, both of the Postgraduate Program in Education - PPGEDu - Institute of Human and Social Sciences - ICHS - UFMT, campus of Rondonópolis, consists of a reflection on the aesthetic experience of babies and small children, from the contact of these with an artistic and playful installation formed by 21 geometric solids (polyhedra , 10 mm thick plywood boxes in the following dimensions: 30 cm and 50 cm edge cubes, 120cm X 50cm X 20cm and 100cm X 40cm X 10cm parallelepideds). It is, therefore, a fieldwork, whose observation is participatory, configuring itself as a research-intervention. On the occasion of the meetings, languages, representations, manifestations of feeling (esthetic), aesthetic actions and expressions of learning through play, constructions and exchanges of experiences between peers were analyzed. The research has phenomenological inspiration, in the mold of american symbolic interactionism, captained by the theoretical conceptions of John Dewey (1978, 2010), interviews between art and sociology, with Ana Mae Barbosa (1975, 1978, 2008 and 2015), William Corsaro (1978, 2010) and John Dewey (1978) (2011) and Manoel Jacinto Sarmento (1997, 2004 and 2009), among other authors. The analyzes made confirm the importance of the artistic experiences in the day care, reason why it was observed of gains for the integral formation of the small participants, when handling the polyhedra. Research is expected to contribute to studies on babies and small children, especially in relation to artistic experiences, which, because of their multifocal nature, constitute affective, aesthetic-esthetic, cognitive, social and political achievements, giving voice, protagonism to the small citizens, events relevant to the construction of the pedagogical identity of Day Care Education and its history.